MITIGASI BENCANA ABRASI PANTAI DI DESA PERMAI KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Ikhwanul Muhtar; Geovani Meiwanda (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
The coastal abrasion disaster that occurred in the Meranti Islands Regency, precisely in the West Rangsang District, Meranti Islands Regency has threatened and brought losses, both in the form of physical and non-physical losses. In 2020, the length of coastal abrasion in Rangsang Barat District will reach 10.75 km2. West Rangsang District is an area located on the coast which has strong wave and wind currents. For this reason, coastal abrasion disasters that occur must be overcome by implementing structural and non-structural mitigation to minimize the risks arising from coastal abrasion disasters that occur. This study aims to look at the implementation of coastal abrasion disaster mitigation and find out the obstacles in mitigating coastal abrasion disasters in Permai Village, Rangsang Barat District. This study uses qualitative research methods with data collection techniques by observation, interviews and documentation. This study has the result that disaster mitigation efforts carried out in Permai Village, Rangsang Barat District have not run optimally. This is due to natural factors and limited budget owned by Permai Village.